Problems of Converting Agricultural Land and the Need to Anticipate Its Control After the Enactment of the Job Creation Law - Mariane, Irene; Sumanto, Listyowati; Probondaru, Ignatius Pradipa; Idris, Siti Hafsyah binti (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2024)
The main problem that farmers face now is the conversion of land function from agricultural to non-agricultural ones because of conflicts of interests. Behind this problem, there is an increase in demand for lands as a result of economic and population growths, leading to food security and import dependence threats. Therefore, protecting agricultural lands becomes more and more urgent to ensure the national food security. This research aims to identify the arising problems regarding the conversion of agricultural land function and the need to anticipate its control upon the enactment of Law Number 11 of 2020 concerning Job Creation. This research applied a normative research method using statute approach. The data it used consisted of primary legal materials such as Law Number 11 of 2020 on Job Creation, and its derivative regulations such as Government Regulations (GR) and one Ministerial Regulation as technical operating references. The data were collected by reviewing the literature and studies, using qualitative analysis, including content analysis to evaluate information objectively. The conclusion was drawn deductively, from general ideas to specific findings. An in-depth investigation was carried out into the relevant legal facts using frame analysis, which limited the scope of studies and attempted to find solutions to the arising issues. The research found that upon the enactment of Job Creation Law, a significant change occurred in the regulations on agricultural land conversion in Indonesia. This led to new challenges in managing the land conversion and required anticipatory measures. Tight monitoring on the agricultural land usage and establishment of a specific institution to manage the state’s agricultural lands are needed. Through farmers’ and community’s active participation, it is expected that the government’s programs can be more responsive to local needs and maximize the use of limited resources.